The utilitarian–maximin social welfare function and anomalies in social choice. (20th September 2020) - Schneider, Mark; Kim, Byung‐Cheol
Abstract: Two major criteria of distributive justice are the utilitarian criterion and the maximin criterion. We offer a simple axiomatic characterization of a mixed utilitarian–maximin social welfare function. This social welfare function explains recent empirical violations of the standard cardinal social choice theory such as the social Allais paradox and the social common ratio effect. In addition, it offers a new foundation for the positively skewed wealth distributions in society. It also provides an objective function for mechanism design applications that trades off maximizing surplus and minimizing inequality.